Analysis of volatile compounds causing undesirable odors in a polypropylene - high-density polyethylene recycled plastic resin with solid-phase microextraction. (December 2020) - Fuller, Jon; White, David; Yi, Huijun; Colley, Jason; Vickery, Zane; Liu, Shaoyang
Abstract: Although recycled plastics provide a low-cost and environmentally friendly alternative for many applications, their desirability is significantly limited by the presence of unpleasant odors from volatile organic compounds (VOCs). In this work, a headspace solid-phase microextraction (HS-SPME) coupled with gas chromatography-mass spectrometry (GC-MS) method was optimized to analyze volatile compounds from an odorous recycled plastic resin which was roughly composed of 85–90% polypropylene (PP) and 15-10% high-density polyethylene (HDPE). A large variety of aliphatic hydrocarbons and 13 additive residues were detected. Statistical tools were employed to screen the VOCs and successfully identified three components, i.e., 2, 4-dimethyl-heptane, 4-methyl-octane and octamethylcyclotetrasiloxane (D4 ), which were significantly related to the odor intensity of the recycled plastic resin (p-values < 0.05). 2, 4-Dimethyl-heptane has a strong, pungent plastic smell, which is very similar to the odor of the recycled resin. It is identified as a major source of the odor. Past relevant research has not been able to establish a direct link between an odorous compound and the undesirable odor of recycled plastic until now. 4-Methyl-octane was highly corelated to 2, 4-dimethyl-heptane and somewhat contributed to the odor. D4 does not have an odor, but it may serve as an indicator of some odorous residues from personal care products. Graphical abstract: Image 1 Highlights: An SPME method was optimized to analyze VOCs of an odorous recycled plastic. Statistical tools were employed to screen VOCs related to the odor. 2, 4-dimethyl-heptane is a major cause of the unpleasant odor. D4 is found to be an indicator of a group of odorous compounds.